دور النشاط الحركي المكيف في خفض القلق لدى البالغين المعاقين حركيا - عثماني اسامة/بن عزوزي داود (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
تهدف هذه الدراسة إلى الكشف عن دور النشاط الحركي المكيف في خفض مستوى القلق لدى البالغين المعاقين حركيا واعتمد الباحث المنهج التجريبي بتصميم المجموعة الواحدة، حيث أجري القياس القبلي والبعدي على عينة قوامها 20 فردًا من البالغين المعاقين حركيا تتراوح أعمارهم بين 18 و45 سنة. كما خضع أفراد العينة لبرنامج في التربية الحركية المكيف تضمن مجموعة من الأنشطة البدنية المصممة وفق مبادئ التدرج والملاءمة لطبيعة الإعاقة وتم جمع البيانات باستخدام مقياس القلق وتحليلها إحصائيًا بواسطة برنامج SPSS وأظهرت النتائج وجود فروق دالة إحصائيًا بين متوسطات القياس القبلي والبعدي لصالح القياس البعدي، مما يدل على فعالية البرنامج في خفض القلق وتحسين التكيف النفسي والاجتماعي وتعزيز الثقة بالنفس وتوصي الدراسة بضرورة إدماج برامج التربية الحركية المكيفة في المؤسسات والمراكز المختصة لما لها من أثر إيجابي على الصحة النفسية والاجتماعية لهذه الفئة. // // // // // Abstract This study aims to explore the role of adapted physical activity in reducing anxiety levels among adults with motor disabilities. The researcher adopted an experimental approach with a single-group design, with pre- and post-tests conducted on a sample of 20 adults with motor disabilities, aged between 18 and 45 years. The sample members also underwent an adapted physical education program that included a set of physical activities designed according to the principles of gradual progression and suitability for the nature of the disability. Data was collected using an anxiety scale and statistically analyzed using SPSS. The results revealed statistically significant differences between the pre- and post-test averages in favor of the post-test, demonstrating the program's effectiveness in reducing anxiety, improving psychological and social adjustment, and enhancing self-confidence. The study recommends the integration of adapted physical education programs into specialized institutions and centers, given their positive impact on the psychological and social health of this group.
LAPA-2025-23
Keywords: النشاط الحركي المكيف; القلق; الاعاقة الحركية; الصحة النفسية; الثقة بالنفس